Analysis of Employment Generation due to Chrysanthemum Cultivation in Mandya District of Karnataka (Indian Journal of Extension Education, 2013)
The study was conducted during the year 2009-2010 in Mandya district of Karnataka. Total employment generation in terms of mandays due to chrysanthemum cultivation was found to be up to 50 mandays which is considered as low and it constitutes around 43.33 per cent followed by 35.00 per cent (51 to 80 mandays) and 21.67 per cent (more than 80 hours) had medium and high category respectively of total employment generation in terms of mandays due to chrysanthemum cultivation. Further, low level of family men labour were used by 43.33 per cent, while low family women labour were used by 45.00 per cent. More than half (52.50%) of hired men labour were utilized and it was 55.00 per cent in case of hired women labour.